Synthesis and production of the antitumor polyketide aurovertins and structurally related compounds - Li, Wei; Ma, Zihui; Chen, Lin; Yin, Wen-Bing (Applied microbiology and biotechnology, 2018)
Aurovertins belong to a family of highly reducing polyketides sharing a polyene α-pyrone-type structure. These compounds comprise aurovertin, asteltoxin, avertoxin, citreoviridin, verrucosidin, and their derivatives, which exihibit potent antitumor, antiviral, and antibacterial activities. Until now, over 40 aurovertins and structurally related compounds have been found in the fungal kingdom. Due to the unique structural feature and interesting bioactivities, significant progresses have been achieved for the structural identification, chemical synthesis, and biosynthesis of the mentioned compounds. Understanding of aurovertin biosynthetic mechanism provides a solid basis for engineering the metabolic pathway of those compounds by rational design and realizing their production in the model fungal host.